Conceptual Framework on E-Marketing in Present Scenario: Exploring the impact of technology and social media on E-marketing strategies (Journal of Advances and Scholarly Researches in Allied Education, 2020)
As outlined in this study, a framework for E-marketing research focuses on both the marketingprocess's tactics and the effectiveness as well as the impact of various technology tools and social mediaplatforms. Using the framework, we have arranged the research techniques about the elements andreviewed the study literature in the widely defined E-marketing area. E-media marketing methods andvarious social media possibilities for marketing will be examined in the research paper. For the most part,this study examines how technology tools and social media platforms contribute to the success of Emarketingstrategies, as well as the relative importance of E-marketing and the distinctions between itand offline marketing. Accordingly, this research paper has been edited to help small businessesincorporate E-advertising into their business models and realize that social media marketing is a moreeffective strategy than traditional advertising methods.